Maternal employment patterns after childbirth and child mental health with 4–6 years of age - Wernecke, Deborah; Peter, Raphael S.; Braig, Stefanie; Genuneit, Jon; Rothenbacher, Dietrich (Frontiers in Psychology, 2025)
ObjectivesTo assess potential associations between maternal employment after childbirth with subsequent child mental health problems.MethodsWe analyzed 536 families of a prospective birth cohort to estimate trajectory classes of maternal employment 0–36 months postpartum. Multivariable linear regression models were employed to examine associations between (1) trajectory classes and (2) maternal employment status at 12 months postpartum with child mental health problems at 4, 5, and 6 years of age.ResultsWe identified five different trajectory classes of maternal employment after childbirth. For boys, trajectory classes 2 and 3 (characterized by relatively high maternal working hours/week) were associated with more mental health problems at ages 5 and 6 compared to class 1 (relatively low or no working hours/week). No associations were found for classes 4 (part-time after 2 years) and 5 (increasing and subsequently decreasing working hours/week) among boys. For girls, class 5 was associated with less mental health problems at ages 5, and 6 compared to class 1. Analysis of maternal employment status at 12 months postpartum showed less mental health problems for part-time employment at 12 months postpartum compared to no-employment among boys.ConclusionMixed results were found for maternal employment after childbirth and boys’ mental health depending on the measure used. No detrimental associations were found for girls.